1997
DOI: 10.1111/j.1440-1681.1997.tb02696.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Salt Loading and High‐calcium Diet on Vascular Smooth Muscle Responses and Endothelium Function in Rats

Abstract: 1. The present study examined the effects of concurrent manipulation of dietary calcium and salt on contractile responses of vascular smooth muscle (VSM) and endothelial function of aortic rings from Sprague-Dawley rats. 2. Salt loading enhanced the contractile response of the aortic rings to noradrenaline (NA), an effect that was blunted by a high calcium intake. 3. Removal of the endothelium and incubation of aortic rings in physiological salt solution containing methylene blue increased the sensitivity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 28 publications
2
25
1
Order By: Relevance
“…In addition, the response of denuded rings to KCl, which induces voltageactivated calcium entry from the extracellular space, and to caffeine, which mobilizes calcium from the sarcoplasmic reticulum, was markedly higher in the HS than in NS group. An increased sensitivity of the vascular smooth muscle cell to vasoconstrictors, such as noradrenaline, was also previously described in rats fed a HS diet (1). It was also reported that vascular reactivity to PE and KCl is greater in endothelininfused rats, particularly when fed a 8% NaCl diet during 9 days, and this was associated with increases in calcium entry from the extracellular space (23).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In addition, the response of denuded rings to KCl, which induces voltageactivated calcium entry from the extracellular space, and to caffeine, which mobilizes calcium from the sarcoplasmic reticulum, was markedly higher in the HS than in NS group. An increased sensitivity of the vascular smooth muscle cell to vasoconstrictors, such as noradrenaline, was also previously described in rats fed a HS diet (1). It was also reported that vascular reactivity to PE and KCl is greater in endothelininfused rats, particularly when fed a 8% NaCl diet during 9 days, and this was associated with increases in calcium entry from the extracellular space (23).…”
Section: Discussionmentioning
confidence: 58%
“…In various strains of rat, a high salt (HS) diet is associated with changes in the reactivity of aortic rings. Many studies conducted in salt-loaded models have shown an increased contraction of vascular smooth muscle cells in response to agonists (1,14). In addition, relaxation evoked by acetylcholine (ACh) or sodium nitroprusside (SNP) was obliterated in aortic rings isolated from adult spontaneously hypertensive and Dalh-sensitive rats fed a 8% NaCl diet for 4 -8 wk (12,14,16).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Many studies showed that sodium overload results in changes in sympathetic reflexes (Miyajima and Bunag, 1985;Ferrari and Mark, 1987) and changes in vascular reactivity (Mulvany et al, 1978;Adegunloye and Sofola, 1997;Nishida et al, 1998;Lenda et al, 2000). Additionally, there are changes in cardiac structure (Lal et al, 2003), function (Simchon et al, 1991), and volume that result in an increased cardiac output.…”
Section: Discussionmentioning
confidence: 98%
“…There are changes in vascular reactivity (Mulvany et al, 1978;Adegunloye and Sofola, 1997;Nishida et al, 1998;Lenda et al, 2000), in sympathetic reflexes (Miyajima and Bunag, 1985;Ferrari and Mark, 1987), on calcium mobilization, in Na + , K + -ATPase activity (Obiefuna et al, 1991a;Li et al, 1994), on endogenous sodium pump ligands levels (Fedorova et al, 2001), and in the balance between blood volume and cardiac output (Simchon et al, 1991).…”
Section: Introductionmentioning
confidence: 97%